ANALISIS SEMIOTIKA KOMUNIKASI NILAI RELIGI DAN NILAI SOSIAL DALAM NOVEL REMBULAN TENGGELAM DI WAJAHMU KARYA TERE LIYE - Amin Rais Dawan; Pramudita Budi Rahayu (Journal of Communication Sciences (JCoS), 2023)
This study analyzes the social and religious values contained in the novel “Rembulan Tenggelam di Wajahmu" by using Ferdinand de Saussure's semiotics theory.This study used a descriptive qualitative approach and employed Ferdinand de Saussure's semiotic analysis theory to analyze social and religious values in the novel. The results showed that social values include affection, not hearting and blaming others, having care,pleasing help,being loyal friends,respecting each other, not replying to evil, being humble,being trusted,doing the best,and respecting other people life. Then, religious values include being honest, trustworthy,consistent,sincere,patienct, forgiving others,and helping each other.